Tramps, trade union travellers, and wandering workers: how geographic mobility undermined organized labour in Gilded Age America - Moody, Kimberly S. (2016)
This thesis will argue that high levels of internal migration in Gilded Age America undermined the stability and growth of trade unions and labour-based parties. Most of the traditional ‘American Exceptionalist’ arguments which asserted a lack of class consciousness will be challenged. Significant weight will be given to the racial, ethnic, and gender divisions within the American working class as a source of relative organizational weakness. As archival sources reveal, however, despite their divisions, workers of all ethnic and racial groups drawn into wage-labour in the Gilded Age often displayed high levels of class consciousness and political radicalism through their actions, organizations, and hundreds of weekly labour papers. They also showed an awareness of the problems of frequent migration or ‘tramping’ in building stable organizations. Driven by the tumultuous conditions of uneven industrialization, millions of people migrated from state-to-state, country-to-city, and city-to-city at rates far higher than in Europe. A detailed analysis of the statistics on migration, work-related travelling, and union membership trends shows that this created a high level of membership turnover in the major organizations of the day—the American Federation of Labour and the Knights of Labour. Confronted in the 1880s with the highest level of migration in the period, the Knights of Labour saw rapid growth turn into continuous decline. The more stable craft unions also saw significant membership loss to migration through an ineffective travelling card system. The organizational weakness that resulted undermined efforts by American workers to build independent labour-based parties in the 1880s and 1890s. ‘Pure-and-simple’ unionism would triumph by the end of the century despite the existence of a significant socialist minority in organized labour.